Basic electronics :Devices,Circuits and It Fundamentals - Kal, Santiram ([S.l.] : Prentice-Hall of India Pvt.Ltd, 2004)
This comprehensive and well organized text discusses the fundamentals of electronic devices and analog and digital circuits, which are so essential for an understanding of communication systems.